Perancangan Ulang Perpustakaan Kota Metro Lampung Dengan Pendekatan Perilaku - Zahra M, Fadhilah; Puspa Nabila, Ganesha; Liritantri, Widyanesti (Telkom University, 2024)
Lampung Metro City Library functions as a place to collect, manage, and store printed and digital papers along with local cultural collections. The library is used as a home for students and the community to find various references or reading materials. In 2023 the Lampung Metro City Library had a target number of visits of 160,519 visitors, but the realization only reached 12,268 visitors. The non-achievement of the target was caused by the low awareness of the community to visit. This happens because the facilities are incomplete and less attractive in design. In addition, the arrangement of space zones and furniture has not provided comfort for users and there is no clarity regarding concepts that adjust the character behavior of each age of users. With these problems, a redesign is needed. The purpose of the redesign is to provide comfort, safety, and attractive designs that have educational value. The methods used in the design and design process are interviews, observations, field studies, documentation, and literature searches or references. The final result of the design is in the form of design implementation based on approaches, themes, and concepts that are adjusted to the problem. Keywords: library, visitors, character, behavior, design